Is hospitalization necessary in isolated traumatic sternal fractures? - Yolgösteren, Atif; Yüksel, Ahmet; Kan, İris İrem and Durak, Vahide Aslıhan (The European Research Journal, 2020)
Objectives: Clinical characteristics, follow-up and treatment outcomes of patients with isolated traumatic sternal fracture were presented and our clinical experiences on these patients were shared. Methods: Between January 2010 and December 2017, a total of 87 patients with isolated traumatic sternal fracture who were admitted to the emergency department and were hospitalized, were included in this observational cohort study. Medical data of these patients were collected from hospital records and then were retrospectively reviewed. Results: There were 65 (74.7%) male and 22 (25.3%) female patients. Mean age was 42.4 ± 13.7 years (range: 17-83). The most common etiological reason was traffic accident in vehicle. Sternal fractures were localized at corpus in 64 (73.6%) patients and at manubrium in 23 (26.4%) patients. The most common concomitant pathology was rib fracture with a ratio of 23% (20 patients). Mean length of hospital stay of patients was 3.1 ± 0.8 days. During the hospitalization period, no evidence of cardiac injury was observed in any patient. Conclusions: In view of rising healthcare costs and increasing demand for acute hospital and intensive care beds, it is crucial to determine hospitalization criteria for cases with traumatic sternal fracture. We believe that the hospitalization is not necessary in isolated traumatic sternal fractures where there is no other major injury.